2017
DOI: 10.18535/jmscr/v5i3.80
|View full text |Cite
|
Sign up to set email alerts
|

Pinna Injuries: Our Experience

Abstract: Introduction: Trauma to the external ear is common, as different kinds of injuries can affect different parts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…In this study majority of patients 34 (42.5%) within age group of 16-25 years and 27 (33.8%) within age group 26-35 years, and this group is considered active population. Similar to Dr Shameem Ahamed, who described a total of 45 cases with ear defects, with bulk of cases within 20-50 years [6]. In comparison to Ravikumar Gopalakrishnan, who studied 24 cases of acquired partial auricular defect and most of the cases were 31-40 years, this study showed slight shift of age group to younger population [7].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In this study majority of patients 34 (42.5%) within age group of 16-25 years and 27 (33.8%) within age group 26-35 years, and this group is considered active population. Similar to Dr Shameem Ahamed, who described a total of 45 cases with ear defects, with bulk of cases within 20-50 years [6]. In comparison to Ravikumar Gopalakrishnan, who studied 24 cases of acquired partial auricular defect and most of the cases were 31-40 years, this study showed slight shift of age group to younger population [7].…”
Section: Discussionsupporting
confidence: 64%
“…Deformity with preserved auricular subunits can be closed primary with respect of auricular curvature, however lost unit need to be replaced by local flap. Vascularity of post auricular tissue enhances flap viability and makes it the best donor site if not scared [6,13]. In this study 32 (40%) patients underwent primary repair, 13 (16.3%) local regional flap and 29 (36.3%) intralesional excision for keloid.…”
Section: Discussionmentioning
confidence: 85%